Observation of Factor XII and Factor XII Deficient Plasma at an Interface - Adams, Ann Lukosevicius; Vroman, Leo (Thrombosis and Haemostasis, 1965)
Ellipsometry recordings and measurements, using wettable anodized tantalum slides (TaW), showed that an adsorbed film of factor XII deficient plasma could be partially removed by adding factor XII to the liquid medium.When factor XII was first adsorbed onto the slide, addition of factor XII deficient plasma caused adsorption followed by partial desorption.Adsorption from a mixture of factor XII and factor XII deficient plasma was followed by spontaneous partial desorption, thus showing a pattern similar to that of intact normal plasma.The ability of a TaW surface to activate intact normal plasma was also demonstrated. The possibility is discussed that the sequence of factors XI and XII adsorption, interaction and desorption, as well as the possible resorption of their activation product, are a function of nature and amount of surface and duration of exposure.